(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2025)
X-ray imaging is a cornerstone of modern medical diagnostics, providing critical insights into the human body’s internal structures. However, the use of X-rays is not without risks. This paper aims to comprehensively review the hazards associated with X-ray imaging, including radiation exposure, biological effects, and safety measures. We also present expanded tables summarizing key data on radiation doses, risk factors, and protective strategies. Additionally, we delve into emerging technologies, regulatory frameworks, and future directions to mitigate risks associated with X-ray imaging.